(untitled) (International Seven Journal of Multidisciplinary, 2023)
In the present investigation, activated carbons were made from peach pits and olive pits. The peach pit was activated with 30% phosphoric acid followed by a heat treatment of 550°C under a controlled atmosphere and the olive pits with hydrogen peroxide H2O2 and potassium hydroxide at 30%. Subsequently, adsorption isotherms were performed to adsorb cyanide, metals and organic compounds from the mining effluents. It was concluded that cyanide adsorbs on the surface of peach and olive pit activated carbon mainly due to the functional groups that coexist on its surface.